Day 2 Wed, August 12, 2015 2015
DOI: 10.2118/174671-ms
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Produced Crude Oil Emulsion in the Presence of ASP

Abstract: The contribution of alkaline/Surfactant/Polymer to the stability of produced crude oil emulsions is neither fully understood nor thoroughly investigated although there have been reports from previous projects that implicate risk produced water treatment. This study focuses on water in oil (w/o) emulsions imposed by ASP flooding for an EOR field in Malaysia to understand the stability of the emulsion layer under typical process conditions. A series of laboratory experiments was conducted to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…It has been reported previously [2,29,30] that ASP produces a highly stable emulsion containing a residual oil-in-water phase which reduces separation efficiency because of the smaller oil droplet size. The most stable emulsion of ASP is selected, and the effect of TiO 2 nanoparticles on the stability of the emulsion is investigated.…”
Section: Asp Emulsion Stability With and Without Tio 2 Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported previously [2,29,30] that ASP produces a highly stable emulsion containing a residual oil-in-water phase which reduces separation efficiency because of the smaller oil droplet size. The most stable emulsion of ASP is selected, and the effect of TiO 2 nanoparticles on the stability of the emulsion is investigated.…”
Section: Asp Emulsion Stability With and Without Tio 2 Nanoparticlesmentioning
confidence: 99%
“…When the droplet size in the emulsion is smaller than 10 µm, it would not be separated by gravitational force and, therefore, it needs to be separated by some other means. A previous study has reported that facility sites of oil fields are experiencing fluid transport problems due to the production of a high amount of crude oil in water, which makes a very stable o/w emulsion in the presence of ASP chemicals [2]. Studies have also reported high stability, higher emulsification, strong interfacial film strength, and a high content of small oil droplets in o/w emulsion [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been reports from previous projects that implicate riskproduced water treatment. A study by Khan et al (2015) focused on water in oil (W/O) emulsions imposed by ASP flooding for an EOR field in Malaysia to understand the stability of the emulsion layer under typical process conditions. Another group of researchers (Kalra et al 2012) have attempted to present the rheology of the problematic water in oil emulsion produced at the facility site.…”
Section: Introductionmentioning
confidence: 99%
“…In the development of enhanced oil recovery in China, the polymer flooding method had been applied successfully . With the injection of chemical floods, breakthrough of the injected chemicals in the primary separator results in the formation of a stabilized water-in-oil emulsion . Emulsion formation and stability also increase when hydrocarbons and formation water are tremendously mixed under high shear from reservoir, tubing, and chokes …”
Section: Introductionmentioning
confidence: 99%